(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age, with a significant impact on reproductive function. This thesis analyzes the main reproductive complications observed in PCOS, including chronic anovulation, infertility, menstrual irregularities, pregnancy-related complications, and their underlying pathogenetic mechanisms. Particular attention is paid to the clinical significance of these complications, as well as to the importance of early diagnosis and comprehensive management strategies in clinical practice.